Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I need to prove following formula:

$|A \cup B|=|A|+|B|-|A\cap B|$

I got so far:

$A=(A\cap B) \cup (A \cap !B)$ // !B should be the complement of B

With this I can get to

$|A|=|A\cap B| + |A \cap !B|$

But I do not have any clue on how to go on. Some advises would be nice.

share|cite|improve this question

Using the same formula on $B$ you have already:

$|A|+|B| = 2|A\cap B|+|A\cap!B|+|A!\cap B| = |A\cap B| + [|A\cap B| + |A\cap !B| + |A!\cap B|]$. The part in $[~]$ can be writen as $|(A\cap B) \cup (A\cap !B) \cup (A!\cap B)|$ which is $|A\cup B|$.

share|cite|improve this answer


$A=(A\setminus B)\cup (A\cap B)$, this is disjoint union; and $B=(B\setminus A)\cup(A\cap B)$, again a disjoint union; and $A\cup B=(A\setminus B)\cup(B\setminus A)\cup(A\cap B)$.

share|cite|improve this answer

If A and B may be infinite, the formula is not valid: Let A= the odd natural numbers, B = the prime numbers, without 2. Then, $|A \cup B| =|A| = |B| = |A \cap B| = \aleph_0$. So, $|A|+|B| = \aleph_0$ and $\aleph_0 - \aleph_0$ is undefined.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.